First-principles screening of structural properties of intermetallic compounds on martensitic transformation. (December 2017) - Lee, Joohwi; Ikeda, Yuji; Tanaka, Isao
Abstract Martensitic transformation with good structural compatibility between parent and martensitic phases are required for shape memory alloys (SMAs) in terms of functional stability. In this study, first-principles-based materials screening is systematically performed to investigate the intermetallic compounds with the martensitic phases by focusing on energetic and dynamical stabilities as well as structural compatibility with the parent phase. The B2, D03, and L21 crystal structures are considered as the parent phases, and the 2H and 6M structures are considered as the martensitic phases. In total, 3384 binary and 3243 ternary alloys with stoichiometric composition ratios are investigated. It is found that 187 alloys survive after the screening. Some of the surviving alloys are constituted by the chemical elements already widely used in SMAs, but other various metallic elements are also found in the surviving alloys. The energetic stability of the surviving alloys is further analyzed by comparison with the data in Materials Project Database (MPD) to examine the alloys whose martensitic structures may cause further phase separation or transition to the other structures. Shape memory alloys: screening from first principles Computationally screening intermetallic combinations for new shape memory alloys can highlight viable options for further investigation. A team led by Isao Tanaka from Kyoto University in Japan screened more than six thousand alloys with stoichiometric combinations for potential shape memory martensite transformation using first-principles. By using existing shape memory alloys to determine screening criteria for working temperature and reversibility of the shape memory effect, they found 187 alloys that show structurally compatible martensitic transformation between the parent and the martensite phase and a stable martensite phase. Of these 187 alloys, none are existing shape memory alloys (as they are not stable enough), and many unlikely elements such as lithium emerge as potential constituent elements. Computational studies may therefore open new avenues for potential alloy compositions showing the shape memory effect.